2015
DOI: 10.1186/s12967-015-0572-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunologic correlates of Melanoma GVAX, a GM-CSF secreting allogeneic melanoma cell vaccine administered in the adjuvant setting

Abstract: BackgroundLimited adjuvant treatment options exist for patients with high-risk surgically resected melanoma. This first-in-human study investigated the safety, tolerability and immunologic correlates of Melanoma GVAX, a lethally irradiated granulocyte–macrophage colony stimulating factor (GM-CSF)-secreting allogeneic whole-cell melanoma vaccine, administered in the adjuvant setting.MethodsPatients with stage IIB-IV melanoma were enrolled following complete surgical resection. Melanoma GVAX was administered int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 60 publications
(60 reference statements)
1
56
0
1
Order By: Relevance
“…(37) In some clinical studies, however, GVAX immunotherapy has lead to a reduction in circulating MDSCs. (38) The relationship between GM-CSF expression and immunoregulatory mechanisms requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…(37) In some clinical studies, however, GVAX immunotherapy has lead to a reduction in circulating MDSCs. (38) The relationship between GM-CSF expression and immunoregulatory mechanisms requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs used for cancer immunotherapy vary both in structure and by mechanism of action. For example, Iipilimumab (anti-CTLA4) directly interacts with and activates immune cells by removing co-inhibitory signal, while GVAX (GM-CSF tumor vaccine) improves tumor recognition by making the tumor more immunostimulatory (Ali and Lee, 2015; Lipson et al, 2015). A recent study by Fiering et al demonstrated the use of iron oxide nanoparticles and an alternating magnetic field to induce local hyperthermia in melanoma.…”
Section: Achievementsmentioning
confidence: 99%
“…230 Regarding the distribution across different cancer types ( Fig. 1), patients harboring melanoma were most commonly enrolled in these trials, 186,196,198,205,213,221,223,227,[231][232][233][234] followed by patients with prostate cancer, 206,208,212,215 glioma or glioblastoma (GBM), 185,197,202,219 hepatocellular carcinoma, 204,211,220 non-small cell lung carcinoma (NSCLC), 207,214,230 renal cell carcinoma (RCC), 201,203 esophageal carcinoma, 216,226 and pancreatic ductal adenocarcinoma, 209,217 among others. Of note, only two trials included a wide range of advanced solid tumors refractory to previous treatments.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%